Manual of auditing - Cooper, Vivian R. V. (London, Gee, 1969)
This book is an attempt to codify audit procedures and the principles which applies in the conduct of the audit practice. This second edition was for updating the audit approach in a number of respects, including adding the substance of the appropriate recommendations issued by The Institute of Chartered Accountants in England and Wales since the first edition was published.
Includes index.
oif 06/02/2019
Ref.
Keywords: Auditing; Auditing---Standards; Great Britain